Redescription of three caligid species of the genus Caligus Müller, 1785 (Copepoda: Caligidae), parasites of marine fish Decapterus sp. (Perciformes: Carangidae) from Tonkin gulf, Vietnam - V. N., Kazachenko; N. N., Kovaleva; Ngo, Ha Duy; Ha, Nguyen Van; Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
So far, parasitic copepods belonging to the family Caligidae on marine fishes in Vietnam have been poorly studied. At present, 250 copepods species belong to the genus Caligus have been registrated in the world, including 54 species recognized in waters of the South East Asia region and 11 species recorded from Vietnam. Based on the specimens of parasite copepods found on the marine fish Decapterus sp. which were collected by scientific researchers of TINRO, Vladivostok Russia from Tonkin gulf, Vietnam in 1960-1961, a re-description of three species of the genus Caligus, viz. Caligus confusus Pillai, 1961, C. constrictus Heller, 1865 and C. robustus Bassett-Smith, 1898 is given. The hosts, distribution and key to the eleven Caligus species for Vietnamese fauna are also provided herein.